1989
DOI: 10.1002/j.1460-2075.1989.tb03434.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the involvement of pim-2, a new common proviral insertion site, in progression of lymphomas.

Abstract: We have compared proviral integrations near (putative) proto‐oncogenes in Moloney murine leukemia virus‐induced primary and transplanted T cell lymphomas. We previously found proviruses integrated near c‐myc, pim‐1, and N‐myc in primary tumors (Selten et al., 1984; Van Lohuizen et al., 1989a; Van Lohuizen et al., 1989b). We have now identified an additional common proviral integration site, called pim‐2, that carries somatically acquired proviruses in the majority of transplanted tumors. In primary tumors inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(62 citation statements)
references
References 20 publications
1
61
0
Order By: Relevance
“…These data suggested that Pim2 is important for tumor progression. 176 Pim1 and Pim2 have been classified in the same group 139 and, in agreement with this, MuLV infection of Pim1/c-Myc bi-transgenic mice targeted Gfi1, not Pim2. 177 The large number of genes identified as Myc collaborators has resulted in attempts to classify these genes into complementation groups.…”
Section: Complementationsupporting
confidence: 66%
“…These data suggested that Pim2 is important for tumor progression. 176 Pim1 and Pim2 have been classified in the same group 139 and, in agreement with this, MuLV infection of Pim1/c-Myc bi-transgenic mice targeted Gfi1, not Pim2. 177 The large number of genes identified as Myc collaborators has resulted in attempts to classify these genes into complementation groups.…”
Section: Complementationsupporting
confidence: 66%
“…The pim-1 proto-oncogene was first identified as a locus frequently activated by proviral integration in Moloney murine leukemia virus-induced mouse T-cell lymphomas (1,2), and pim-2 was identified as a gene frequently activated in secondary transplants of virus-induced lymphomas. PIM-3 was identified as a PIM-1-and PIM-2-related kinase (3). The oncogenic nature of PIM-1 and PIM-2 was confirmed by the observation that transgenic mice overexpressing these kinases in the lymphoid system develop lymphomas.…”
Section: Introductionmentioning
confidence: 93%
“…Tumour DNA was screened for rearrangements in known oncogenes using DNA probes as follows: N-Myc, 450 bp PCR fragment (Baxter et al, 1996); Pim1, 835 bp PCR fragment from clone pPim1 (Cupyers et al, 1984); Pim2, 2.05 kb cDNA fragment (van der Lugt et al, 1995); Tic1, 1.3 kb PCR fragment from clone pMB20 (Breuer et al, 1989); Pal1, 1.45 kb PCR fragment from clone p11A2 (van Lohuizen et al, 1991); Bmi1, 596 bp PCR fragment from cDNA 13.1 (van Lohuizen et al, 1991); G®1, 1.5 kb XbaI/BamHI cDNA fragment (Gilks et al, 1993); Dsi1, 4 kb BamHI/EcoRI fragment corresponding to the dsi-SR probe (Vijaya et al, 1987); Evi5, cDNA probe (Liao et al, 1995); Ahi1, 800 bp PstI/HindIII fragment from clone p2-1 (Poirier et al, 1988); Runx1, 158 bp PCR fragment derived from the exon 1 of the RUNX1c isoform (Miyoshi et al, 1995). c-Myc rearrangements were identi®ed using a human c-MYC exon 3 probe, (Stewart et al, 1993) which cross hybridises with the murine c-Myc gene due to the high degree of homology between the human and murine genes.…”
Section: Dna Hybridization Analysismentioning
confidence: 99%